Accuracy of Static Computer-Assisted Implant Placement in Narrow Ridge by Novice Clinicians - Abduo, Jaafar; Hasan, Radhwan Himmadi; Lau, Douglas (European Journal of Dentistry, 2025)
This study aimed to evaluate the accuracy and clinical impact of implant placement by novice implant clinicians in the narrow anterior ridge by fully guided (FG), pilot-guided (PG), and freehand (FH) placements.A maxillary surgical model with missing incisors and a narrow ridge was designed. Two implants were planned in the lateral incisor locations to receive screw-retained implant prosthesis. Fifteen novice implant clinicians placed implants according to every placement. Angle, vertical and horizontal platform, and horizontal apex deviations from the planned implant were measured. The clinical impact evaluation aimed to relate the position of each placed implant to (1) periimplant bone dimension after implant placement and (2) the prosthesis retention mechanism.The FG implants were more accurate than PG implants at the angle (p = 0.001) and maximum horizontal apex deviations (p = 0.001), and were more accurate than FH implants for all comparisons (p = 0.001). The PG implants were superior to FH implants at the maximal horizontal platform deviation (p = 0.001). All FG implants were fully covered with bone and could be restored with screw-retained prostheses. One PG implant (3.3%) had fenestration at the apex, and one PG implant (3.3%) could not be restored with screw-retained prosthesis. Seven FH implants (23.3%) had fenestration at the apex, and one FH implant (3.3%) suffered from dehiscence. Seven FH implants (23.3%) were not restorable with screw-retained prosthesis.For novice clinicians, a significantly greater accuracy was observed for FG placement, followed by PG and FH placements. FH implants experienced significant compromise of periimplant bone dimension and the prosthesis retention mechanism.
Keywords: computer-assisted; guided surgery; implant surgery; surgical guide